Maternal obesity alters uterine NK activity through a functional KIR2DL1/S1 imbalance. Issue 8 (16th April 2018) - Castellana, Barbara; Perdu, Sofie; Kim, Yoona; Chan, Kathy; Atif, Jawairia; Marziali, Megan; Beristain, Alexander G
Abstract: In pregnancy, uterine natural killer cells (uNK) play essential roles in coordinating uterine angiogenesis, blood vessel remodeling and promoting maternal tolerance to fetal tissue. Deviances from a normal uterine microenvironment are thought to modify uNK function(s) by limiting their ability to establish a healthy pregnancy. While maternal obesity has become a major health concern due to associations with adverse effects on fetal and maternal health, our understanding into how obesity contributes to poor pregnancy disorders is unknown. Given the importance of uNK in pregnancy, this study examines the impact of obesity on uNK function in women in early pregnancy. We identify that uNK from obese women show a greater propensity for cellular activation, but this difference does not translate into increased effector killing potential. Instead, uNK from obese women express an altered repertoire of natural killer receptors, including an imbalance in inhibitory KIR2DL1 and activating KIR2DS1 receptors that favors HLA‐C2‐directed uNK activation. Notably, we show that obesity‐related KIR2DS1 skewing potentiates TNFα production upon receptor crosslinking. Together, these findings suggest that maternal obesity modifies uNK activity by altering the response toward HLA‐C2 antigen and KIR2DL1/2DS1‐controlled TNFα release. Furthermore, this work identifies alterations in uNK function resulting from maternal obesity that may impact early developmental processes important in pregnancy health. Abstract : The effect of maternal obesity on uterine natural killer cell (uNK) function in early pregnancy is unknown. This study identifies that maternal obesity associates with increased uNK activity characterized in part by an imbalance in KIR2DL1/KIR2DS1 expression that drives altered production of TNFa. This work shows how obesity in pregnancy affects uNK function and activity.